Antimicrobial resistance surveillance of Clostridioides difficile in Australia, 2015–18. (25th April 2021) - Putsathit, Papanin; Hong, Stacey; George, Narelle; Hemphill, Christine; Huntington, Peter G; Korman, Tony M; Kotsanas, Despina; Lahra, Monica; McDougall, Rodney; McGlinchey, Andrew; Moore, Casey V; Nimmo, Graeme R; et al.
Abstract: Background: Clostridioides difficile was listed as an urgent antimicrobial resistance (AMR) threat in a report by the CDC in 2019. AMR drives the evolution of C. difficile and facilitates its emergence and spread. The C. difficile Antimicrobial Resistance Surveillance (CDARS) study is nationwide longitudinal surveillance of C. difficile infection (CDI) in Australia. Objectives: To determine the antimicrobial susceptibility of C. difficile isolated in Australia between 2015 and 2018. Methods: A total of 1091 strains of C. difficile were collected over a 3 year period by a network of 10 diagnostic microbiology laboratories in five Australian states. These strains were tested for their susceptibility to nine antimicrobials using the CLSI agar incorporation method. Results: All strains were susceptible to metronidazole, fidaxomicin, rifaximin and amoxicillin/clavulanate and low numbers of resistant strains were observed for meropenem (0.1%; 1/1091), moxifloxacin (3.5%; 38/1091) and vancomycin (5.7%; 62/1091). Resistance to clindamycin was common (85.2%; 929/1091), followed by resistance to ceftriaxone (18.8%; 205/1091). The in vitro activity of fidaxomicin [geometric mean MIC (GM) = 0.101 mg/L] was superior to that of vancomycin (1.700 mg/L) and metronidazole (0.229 mg/L). The prevalence of MDR C. difficile, as defined by resistance to ≥3 antimicrobial classes, was low (1.7%; 19/1091). Conclusions: The majority of C. difficile isolated in Australia did not show reduced susceptibility to antimicrobials recommended for treatment of CDI (vancomycin, metronidazole and fidaxomicin). Resistance to carbapenems and fluoroquinolones was low and MDR was uncommon; however, clindamycin resistance was frequent. One fluoroquinolone-resistant ribotype 027 strain was detected.